Fases Geométricas e suas relações com a Teoria de Fibrados e Representação de Grupos. - Carvalho Neto, Osvaldo Fernandes (2008)
We present the own mathematic formalism to, first of all, study the holonomy interpretations of the adiabatic geometric phase presented by Berry-Simon and Aharanov-Anadan and, after this, the similirities found with the theory of representation groups, particularly, with the Borel-Weil-Bott theorem. These relations are made through classification of complex bundle line, and these results are used to introduce a cranked Hamiltonian. In general, we also show that the parameter space is a flag manifold or a submanifold of her and present a topologic argument of this space that indicates the relation between the structure Riemannian and the Berry s connection.